2019
DOI: 10.15575/ijni.v7i2.12533
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dakwah Pattern Method Development in School Students

Abstract: This research is motivated by a decline in morals which is increasingly widespread in this millennial era. The development of information technology that has entered the industrial revolution 4.0 has a huge impact on the behavior and culture that develops in society. Apart from positive things, of course the negative impacts are due to the very openness of information that can be accessed by all people, including children. Among them are the many hoaxes and trash information as well as misleading information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Based on the research results, it was found that IHAQI SMP Creative Islamic Boarding School has good management in its implementation da'wah pattern guidance method . Planning uses the da'wah pattern as a learning method carried out by educators at the IHAQI Boarding School Creative Middle School (Yusuf et al, 2019) . The Zotero app is used for citations and APA 7th (American Psychological Association 7th edition) as reference style.…”
Section: Civil Village Communitymentioning
confidence: 99%
“…Based on the research results, it was found that IHAQI SMP Creative Islamic Boarding School has good management in its implementation da'wah pattern guidance method . Planning uses the da'wah pattern as a learning method carried out by educators at the IHAQI Boarding School Creative Middle School (Yusuf et al, 2019) . The Zotero app is used for citations and APA 7th (American Psychological Association 7th edition) as reference style.…”
Section: Civil Village Communitymentioning
confidence: 99%